Essential qualities that should be emphasized in the professional training of competent trade teachers - Pugne, Melquiades F. 1922- ([Quezon City s.n.], 1962)
This paper identifies the qualities that should be emphasized in the professional training of candidates to become competent trade teachers. It includes the qualities that are regarded to be very important by the trade school administrators and the similarities of these qualities with those that are considered essential by writers and authors in trade and industrial education.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Vocational education; Teachers, training of